The Impact of Financial risks in the Degree of Banking Safety in Private Commercial Banks in Syria "Case study of the Bank Audi Syria for the period (2010-2018) (Journal of Hama University, 2020)
This study aims to identify the impact of financial risks in the degree of banking safety in private commercial banks in Syria, the case study of Bank Audi Syria for the period from 2010 to 2018. The importance of this study is to highlight the importance of measuring financial risks and their impact on the degree of banking safety which considered  one of the main objectives of commercial banks.The independent variable represents the financial risk (liquidity risk and credit risk)while the dependent variable represents bank safety and is measured by the ratio of equity to risk assets, and to study the relation between them, the descriptive approach was adopted. The simple regression method was used based on the statistical analysis program SPSS21.The results of the study showed a strong positive correlation between liquidity risk and bank safety, as well as a strong but adverse correlation between credit risk and bank safety, and a statistically significant effect for liquidity risk and credit risk in the degree of banking safety